Integrasi Teknologi dalam Proses Pembelajaran : Peluang, Tantangan, Strategi - Puja Aulia; Mhd Subhan; Azian Fajri Fiqori; Sherly Indriani; Gladis Salsabilla Bangun (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the opportunities, challenges, and strategies for integrating technology into the learning process. The research is based on the reality that digital technology has significantly transformed the educational landscape. The study employed a literature review and content analysis method using a qualitative approach. Data were collected from various secondary sources such as academic journals, research reports, and relevant literature. The findings indicate that integrating technology into learning offers several opportunities, including improved access to information, support for independent and collaborative learning, and enhanced efficiency in assessment. However, there are notable challenges, including digital inequality, limited infrastructure, and low digital literacy among educators. Therefore, effective strategies such as teacher training, infrastructure reinforcement, the adoption of flexible learning models, and continuous evaluation must be implemented to optimize technology use in education. In conclusion, well-planned and inclusive technology integration has the potential to significantly improve the quality of education.